Chronic Subthreshold Cortical Stimulation for Adult Drug Resistant Focal Epilepsy: Safety, Feasibility, and Technique - Kerezoudis, Panagiotis (J Neurosurg, 2017)
OBJECT: Epilepsy surgery is effective for lesional epilepsy but can be associated with significant morbidity when seizures originate from eloquent cortex that is resected. Here, the objective is to describe chronic subthreshold cortical stimulation and evaluate its early surgical safety profile in adult patients with epilepsy originating from seizure foci not amenable to surgical resection. METHODS: Adult patients with focal drug resistant epilepsy underwent intracranial electroencephalography monitoring for evaluation of surgical resection. Those with seizure foci in eloquent cortex were not resection candidates and were offered a short therapeutic trial of continuous subthreshold cortical stimulation via intracranial monitoring electrodes. After a successful trial, electrodes were explanted and permanent stimulation hardware was implanted. RESULTS: Ten adult patients (6 males) from 2014 to 2016 were included. Intracranial pathologies included: cortical dysplasia (n = 3), encephalomalacia (n = 3), cortical tubers (n = 1), Rasmussen encephalitis (n = 1) and linear migrational anomaly (n = 1) based on radiographic imaging. The duration of intracranial monitoring ranged from 3–20 days. All patients experienced an uneventful postoperative course and were discharged home with median length of stay 10 days. No postoperative surgical complications developed (median length of follow-up: 7.7 months). Seizure severity and seizure frequency improved in all patients. CONCLUSION: Our institutional experience shows that chronic subthreshold cortical stimulation can be safely and effectively performed in appropriately selected patients without postoperative complications in this small group. Future investigation will provide further insight to recently published results regarding mechanism and efficacy of this novel and promising intervention.